UPAYA MENINGKATKAN KEMAMPUAN MEMBACA, MENULIS DAN MENGHITUNG MELALUI REMEDIAL TEACHING BAGI ANAK TUNAGRAHITA RINGAN DI WISMA PAULO 6 YAYASAN BHAKTI LUHUR MALANG - Sri Wahyuni; Florentina Muliati (Jurnal Pelayanan Pastoral, 2022)
A mild mentally retarded child is a mentally retarded child who is unable to attend regular school programs but still has abilities that can be developed through special education. Remedial Teaching is an educational service or a form of learning program that is carried out with special treatment given by the teacher to students who experience difficulties and obstacles in teaching and learning activities so that these students achieve predetermined competency standards. This study aims to determine whether remedial teaching can improve reading, writing and counting skills for mild mentally retarded children at Wisma Paulo 6 Yayasan Bhakti Luhur Malang. This study uses a quantitative descriptive research design, with the subject of 2 children with mild mental retardation. The method used is full participant observation. While the data analysis is done by comparing the initial test and the final test. In accordance with the aim of efforts to improve reading, writing and counting skills for mild mentally retarded children, the following results were obtained: for MZ respondents in reading practice the pre test score was 5, the post test score was 8, so there was 3 points progress. For practice writing, the pre-test score is r 5 and the post-test score is 9, so there is a 4-point progress. For practice calculating the pre-test score is 5 and the post-test result is 8, so there is a progress of 3 points. For AG respondents, the pre-test scores were 5 and the post-test scores were 9, so there was a 4-point progress. For practice writing, the pre-test score is 5 and the post-test score is 9, so there is a 4-point progress. For practice calculating the pre-test scores and the post-test results are 8, so there is a progres of 3 points.